An Empirical Investigation in Turkish Mobile Network Market - Havvanur Feyza Kaya; Selahattin Kaynak (Current Perspectives in Social Sciences, 2024)
The purpose of this study is to investigate the impacts of total subscribers, net investment, mobile data traffic, and mobile number portability on the net sales revenues. In this study, the effects of total subscribers, net investment, mobile data traffic, and mobile number portability on the net sales revenues are tested by using Generalized Method of Moments. The data cover the period of 2010:01-2019:03 (quarterly) for Turkish mobile network market. The Turkish mobile network market is dominated by the three major firms Turkcell, Vodafone, and Avea. According to findings of this study, the most efficient variable that affects net sales revenues is the total mobile data traffic in Turkcell. However, the most efficient variable that affects net sales revenues is the number of total subscribers in Vodafone and Avea. While the number of total subscribers does not have a statistically significant effect on net sales revenues in Turkcell, does significant effect on net sales revenues in Vodafone and Avea. Also, total mobile data traffic does not have effect on the net sales revenues in Avea, but others.